PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL DISCOVERY LEARNING DENGAN MEMPERHATIKAN BEBAN KOGNITIF PADA MATERI TRIGONOMETRI KELAS X SMK - Setiawan, Toto' Bara; Suharto, Suharto; Susanto, Anas (Kadikma, 2016)
Abstrak. This research aims to (1) analyze the development process of mathematics learning media with discovery learning model by paying attention to cognitive load in trigonometry subject at tenth grade of vocational high school; (2) analyze the development result of mathematics learning media with discovery learning model by paying attention to cognitive load in trigonometry subject at tenth grade of vocational high school. Mathematics learning media that were development are Lesson Plan and students’ worksheet. This research took place at tenth grade KIA 2 of vocational high school 5 jember with consists 36 students. This research is development research. Process and result from development were (1)the development process of using modified thiagarajan model which consists of 3 stages; (2) development result were validation test from validation sheet analysis that scored 3,80 for Lesson plan validatiy coefficient and 3,83 for Student work sheets validatiy coefficient with valid category, practicality test from teacher’s activity analysis scored 89,74% for the first meeting and 94,87% for the second meeting with good category, and efectiveness test from students activity analysis, Learning Result Test and students’ questionnaire analysis with effective result. Result of this mathematics learning media development showed that discovery learning mathematics learning media by paying attention to cognitive load fulfilled validity, praticality, efectiveness so that it can be used well for learning. Keyword: Development, Media, Cognitive Load Theory, Trigonometry